Effect of end milling parameters on MRR and hardness variation of AA7075. (2023) - Jayakumar, K.; Abdul Rahman, PJ.
Abstract: The end milling process is a bulk machining process used for machining an edge surface on the part, making slots, pockets, dies and moulds. Aluminium alloy 7075 (AA7075) is an alloy, with zinc as the principal alloying element. It shows good ductility, high strength, toughness, and fatigue resistance. It is one of the most used aluminium alloys for highly stressed structural applications and is widely applied in aircraft structural parts. By considering the application of AA7075 and uses of the milling process in product manufacturing, the present work focuses on studying the effect of End milling process parameters in the milling of AA7075 plate by varying three distinct parameters: Cutting speed (S), Feed (f) and Depth of cut (d). The output parameters measured were Material Removal Rate (MRR) and Hardness (BHN) variation on the machined surfaces. The BHN of the machined surfaces varied from 178 to 260 BHN. Similarly, the MRR varied from 1500 to 13200 mm 3 / sec . The down milling experiments were conducted as per Taguchi's L9 orthogonal array on a 6 mm thick plate using a solid carbide end mill cutter of 10 mm diameter. The effect of milling process parameters on selected responses was analyzed, and the optimization of process factors for maximization of MRR and hardness was carried out to improve the machinability of AA7075 alloy.